Digital Journalism: A Shift in Journalistic Activity from News Television Media to Social Media (Study on Kompas TV) - Idamana Banjiwo; Irwansyah Irwansyah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The presence of technology and the internet in the world has brought many changes, even affecting the way people communicate and interact. In Indonesia now has more than 170 million internet users, meanwhile the number of social media users is 160 million. This large number of social media users is also being used by news television media as a new platform for disseminating news. Now news is no longer conventionally distributed through public frequencies, but has also been distributed through digital media such as social media, giving rise to a new term called digital journalism. Conditions like this have an impact on journalism activities that have shifted from the news production process to news distribution.In the production process, journalists are no longer fixated on news value, but based on trends that are being discussed by the public on social media. News sources can not only be obtained through field observations and interviews with sources, but also make social media a source of news. In the era of digital journalism, journalists are no longer the only source of news. People can now get information from anyone on social media. For this condition journalists are given greater responsibility in disseminating correct information so that the public knows where to go to get the truth about an event